Study of the Contrast Observed on Carbon by Monte Carlo Simulation on wet-STEM Tomography - Septiyanto, Rahmat Firman; Affifah, Isriyanti (Computational And Experimental Research In Materials And Renewable Energy, 2022)
Analyzing the structure of the material in the fields of material science needs a very good device and methods. Due to its principle in projected images at various tilt angles and calculation of the three-dimensional volume reconstruction with a distinct algorithm, tomography become an excellent tool for analyzing the 3D structure. Several research has been studied to apply electron tomography in ESEM (Environmental Scanning Electron Microscopy) which gives an opportunity in observing the wet material (hydrated) in the aquatic environment. In this research, we showed the advisability of wet-Carbon compound tomography by simulating the interaction of electron materials. Monte Carlo simulation was applied in this study to calculate the optimum water layer thickness in the wet material detected.Keywords: Carbon, Electron Tomography, Simulation of Monte Carlo, STEM